Aspects of solid waste management : Bangladesh context - Hoq, Mofizul; Lechner, H.; Goethe-Institut Dhaka (Dhaka : German Cultural Centre, 1994)
Papers presented at an International Workshop on Waste Management in Asian Cities held on April 8-11, 1993 under the sponsorship of German Cultural Centre.
Includes bibliographical references.
Keywords: Refuse and refuse disposal -- Bangladesh -- Congresses